+0  
 
 #1
avatar+91112 
+1

We can use this formula to find each new point

 

new point  = (old point - center)*scale factor + center

 

So

[ (-1, 3) - ( -2 , -2) ] * 2 + (-2, -2)  = [ 1 , 5 ] *2 + (-2,-2)  = (2, 10) + (-2, -2)  = (0, 8)

 

[ (-5, 2) - ( -2, -2) ] *2 + (-2, -2)  =  [ -3, , 4]*2 + (-2,-2)  = ( -6, 8 ) + (-2, -2) = (-8, 6)

 

[(-4, -2) - (-2, -2) ] *2 + (-2, -2)  = [ (-2, 0) ]*2 + (-2, -2)  = (-4, 0) + (-2, -2) = (-6, -2)

 

[ (1,1) - (-2, -2)]*2 + (-2,-2)  = [ (3, 3]*2 + (-2, -2)  = (6, 6) + (-2, -2)  = (4, 4) 

 

Here's a pic :

 

 

cool cool cool

CPhill  Oct 18, 2018
edited by CPhill  Oct 18, 2018

8 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.